Fish standard length of Gobius incognitus individuals used for the mutual transplant between an ambient (380 μatm) and high (850 μatm) CO2 site off a volcanic CO2 vent in Vulcano island, Italy - Davide Spatafora; Carlo Cattano; Giorgio Aglieri; Federico Quattrocchi; Gabriele Turco; Piero Calosi; Marco Milazzo (PANGAEA, 2023)
Fish standard length (cm) of Gobius incognitus individuals used for a mutual transplant experiment (Ambient-Ambient, High CO2-Ambient, High CO2-High CO2, Ambient-High CO2). Standard length was measured from digital photographs, using a ruler as a reference with the ImageJ software.